A Conceptual Model for Explaining Supply Chain Performance in Uganda’s SMEs - Tukamuhabwa, Benjamin R (Information Management and Business Review, 2011)
This study proposes a conceptual framework, which will be used to conduct an empirical study of supply chain performance in SMEs in Uganda. This conceptual framework was developed from the review of the previous literature. The need for this study arises from the fact that where as SMEs form the back borne of Uganda’s economy, they have encountered poor supply chain performance. Previous researchers also indicate that studies in SMEs and their supply chains are limited and that more research is needed regarding the link between marketing and supply chain management. The proposed conceptual framework presupposes a positive relationship between market orientation and supply chain performance with organizational learning, supply chain management strategy, trust and commitment playing mediating roles. It is hoped that this proposed integrative conceptual model will also be used in other future empirical studies.